Agrobacterium- and a single Cas9-sgRNA transcript system-mediated high efficiency gene editing in perennial ryegrass - Kumar, Rahul; Kamuda, Troy; Budhathoki, Roshani; Tang, Dan; Yer, Huseyin; Zhao, Yunde; Li, Yi (Frontiers in Genome Editing, 2022)
Genome editing technologies provide a powerful tool for genetic improvement of perennial ryegrass, an important forage and turfgrass species worldwide. The sole publication for gene editing in perennial ryegrass used gene-gun for plant transformation and a dual promoter based CRISPR/Cas9 system for editing. However, their editing efficiency was low (5.9% or only one gene-edited plant produced). To test the suitability of the maize Ubiquitin 1 (ZmUbi1) promoter in gene editing of perennial ryegrass, we produced ZmUbi1 promoter::RUBY transgenic plants. We observed that ZmUbi1 promoter was active in callus tissue prior to shoot regeneration, suggesting that the promoter is suitable for Cas9 and sgRNA expression in perennial ryegrass for high-efficiency production of bi-allelic mutant plants. We then used the ZmUbi1 promoter for controlling Cas9 and sgRNA expression in perennial ryegrass. A ribozyme cleavage target (RZ) site between the Cas9 and sgRNA sequences allowed production of functional Cas9 mRNA and sgRNA after transcription. Using Agrobacterium for genetic transformation, we observed a 29% efficiency for editing the PHYTOENE DESATURASE (PDS) gene in perennial ryegrass. DNA sequencing analyses revealed that most pds plants contained bi-allelic mutations. These results demonstrate that the expression of a single Cas9 and sgRNA transcript unit controlled by the ZmUbi1 promoter provides a highly efficient system for production of bi-allelic mutants of perennial ryegrass and should also be applicable in other related grass species